VD_FINDINFO AI 18/15 - 65/2016 vom 1. März 2016 - VD Tribunal cantonal (2016)
RAPPORT MÉDICAL, FORCE PROBANTE, EXPERTISE, DÉCISION DE RENVOI | 28 LAI, 59 al. 3 LAI, 59 al. 5 LAI, 43 LPGA, 44 LPGA, 61 LPGA, 8 LPGA, 49 RAI